2020
DOI: 10.1097/ncc.0000000000000820
|View full text |Cite
|
Sign up to set email alerts
|

3 Dimensions of Treatment Decision Making in Adolescents and Young Adults With Cancer

Abstract: This dissertation is dedicated to my family, who provided me unconditional support and love during this journey through my doctoral education: my children, David, Laura and John and my husband, Paul. v Acknowledgements There are so many people to whom I am very grateful for their assistance, support and mentoring during my doctoral education. I am especially thankful to the following individuals: Dr. Roberta Rehm, my faculty advisor and dissertation chair, whose wisdom and gentle guidance has been invaluable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 89 publications
2
59
0
Order By: Relevance
“…Our review complements the work of Pyke-Grim et al, 16 by applying a HL lens and identifying social and contextual issues relevant to AYAs and how they influence decision-making. This is illustrated in our modified AYA framework, which recognizes the complex, variable, and dynamic nature of triadic decision-making between AYAs, families, and clinicians.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Our review complements the work of Pyke-Grim et al, 16 by applying a HL lens and identifying social and contextual issues relevant to AYAs and how they influence decision-making. This is illustrated in our modified AYA framework, which recognizes the complex, variable, and dynamic nature of triadic decision-making between AYAs, families, and clinicians.…”
Section: Discussionmentioning
confidence: 78%
“…The identified themes suggested that family members and clinicians were prominent in facilitating higherorder HL skills such as understanding and using information to A recent systematic review of qualitative, quantitative, and mixed methods studies examined decision-making involvement in AYAs. 16 Participation was found to be an ongoing process impacted by situational moderators, including developmental stage, chronological age, disease state and recency of diagnosis, type of decision, decisional context, and family context. 16 These findings highlight the considerable heterogeneity and complexity of factors influencing AYAs' current or preferred involvement in their healthcare decisions across the illness trajectory at the time of their transition into adulthood.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations